Posterior capsular infiltration with local anaesthetic cocktail during total knee arthroplasty: a prospective comparative study - Shah, Vikram I.; Pachore, Javahir A.; Patil, Jayesh; Rajani, Darshan (International Journal of Research in Orthopaedics, 2022)
Background: Total knee arthroplasty offers a stable joint with excellent long-term results in osteoarthritis knee patients. The procedure is also associated with post-operative pain which can lead to delayed functional recovery in few patients. This comparative study was aimed to evaluate the effiсасy of а lосаl anaesthetic сосktаil injection with and without роsteriоr сарsulаr infiltration for роst-орerаtive раin соntrоl and early functional reсоvery in раtients undergoing simultaneous bilateral TKА. Methods: This was a prospective comparative study which involved 50 participants undergoing bilateral TKA where one knee, received LIA in anterior, medial and lateral structures of the knee as well as posterior capsule (group A) and contralateral knee received LIA in anterior, medial and lateral structures, identical to the former knee, but excluding posterior capsule region (group B). Pre-operative and post-operative parameters such as VAS, KSS and knee ROM in both knees of all the patients were noted and compared to evaluate the efficacy of PCI. Results: Comparison of VAS scores, post-operatively showed that VAS on rest and on movement was lower in group A than group B at all the time frames (p value <0.0001*). Post-operative knee ROM was higher in group A (p<0.0001). Knee society score was observed to be higher in group A than group B on 15th day and at 1 month (p<0.0001). Conclusions: The study successfully demonstrates that posterior capsular infiltration when included in LIA technique provides a better pain control and also early functional recovery after TKA.